2005
DOI: 10.3168/jds.s0022-0302(05)73121-0
|View full text |Cite
|
Sign up to set email alerts
|

Processing Whole Cottonseed Moderates Fatty Acid Metabolism and Improves Performance by Dairy Cows

Abstract: Pelleting cottonseed (CS) improves handling characteristics. Our objectives were to determine whether increasing the particle size of the CS pellet or dilution of a smaller pellet with delinted CS would limit the rate of CS oil release to optimize digestibility of fatty acids (FA) and fiber while maintaining milk fat production. In a 5 x 5 Latin square design with 3-wk periods, 5 rumen-cannulated cows were fed 1) control with CS hulls (CSH) and CS meal plus tallow and Ca soaps of FA, 2) whole CS (WCS), 3) smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 40 publications
8
15
0
Order By: Relevance
“…These results were consistent with other reports (Dhiman et al, 1999;Moreira et al, 2004;Reveneau et al, 2005).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…These results were consistent with other reports (Dhiman et al, 1999;Moreira et al, 2004;Reveneau et al, 2005).…”
Section: Resultssupporting
confidence: 94%
“…However, we observed that the milk protein was increased when cows were fed delinted and extruded WCS (P<0.05), which was consistent with some previous reports (Mabjeesh et al, 2000;Reveneau et al, 2005). This can be explained that microbial protein synthesis was improved when cows were fed processing WCS, resulting in an increase of protein fl ow in the small intestine.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…There was a trend that diets supplemented with extruded WCS could increase NDF digestibility (P<0.1). This result was in agreement with previous reports (Pires et al, 1997;Reveneau et al, 2005;Sullivan et al, 2005). The decrease in nutrient solubility and degradability of extruded WCS may increase passage of fi bre of WCS origin to the abomasum.…”
Section: Resultssupporting
confidence: 83%